SMART-Learning School Information System: A Design Science-Based Framework for IT Governance and Auditing in Senior High Schools (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study addresses the persistent lack of structured, education-specific information technology (IT) governance and auditing frameworks within Senior High Schools (SHSs). While corporate entities heavily leverage mature frameworks such as COBIT 2019 to enforce accountability, maintain system stability, and guarantee security compliance, secondary education systems frequently manage fragmented implementations of Learner Information Systems (LIS) and Learning Management Systems (LMS) devoid of equivalent oversight. Guided by Design Science Research (DSR), this study develops and evaluates the SMART - Learning School Information System (SMART - LSIS) Framework. The framework provides a structured approach to IT governance and auditing, designed to enhance management, monitoring, and accountability of school information systems in Senior High Schools.A purposive sample of 25 school ICT stakeholders - including ICT Coordinators, School Administrators, Registrars, and Support Staff - evaluated the institutionalized system infrastructure across five core domains. Descriptive statistical analysis revealed a Grand Mean of 4.05 (Agree), demonstrating strong stakeholder validation regarding the utility and structural composition of the artifact. However, Gap Analysis exposed a critical vulnerability: IT Auditing exhibited the lowest evaluation score (M = 3.87) and the highest discrepancy relative to the ideal standard (Gap = 1.13). These empirical insights substantiate the necessity of an integrated framework to consolidate school governance, system tracking, risk mitigation, and performance monitoring into a unified, continuous-improvement architecture.